DIVERSIVIKASI PRODUK OLAHAN PISANG SEBAGAI STRATEGI PEMBERDAYAAN EKONOMI LOKAL: STUDI PENGABDIAN MASYARAKAT DI DESA PEMEPEK, LOMBOK TENGAH - Petrunella, Ruth Stella; Hidayat, Muhamad Aldin; Yakin, Yusril Hakkul; Magfira, Risqa; Jannah, Gina Raudatul; Hikmah, Nurul; Wulandari, Nadiya; Nurhidayanti, Asri; Malik, Ilham; Seftiawati, Niza Ervia; Ilham, Muhammad Wayudi (Universitas Mataram, 2025)
The Community Service Program (KKN PMD) of the University of Mataram in Pemepek Village, Pringgarata Subdistrict, Central Lombok, focuses on community empowerment through banana-based product innovation. Pemepek village has abundant agricultural potential, especially bananas, which are often underutilized. In collaboration with the Mekar Harum Women’s Farmer Group (KWT), the KKN team introduced training on making banana steamed cake and banana ice cream as potential flagship products. The results indicated strong enthusiasm from KWT members, particularly for banana ice cream production, whish is targeted for sale in schools and households. This program not only creates new business opportunities for village women but also helps increase household income with relatively low capital. These findings highlight that local food product innovation can serve effective strategy to enhance community economy while strengthening the village’s identity on local potential.